Biosynthetic gene clusters guide rational antibiotic discovery from Actinomycetes - Culp, Elizabeth (My University, 2020)
As the spread of antibiotic resistance threatens our ability to treat infections, avoiding the return of a pre-antibiotic era urgently requires the discovery of novel antibiotics. Actinomycetes, a family of bacteria commonly isolated from soil, are a proven source of clinically useful antibiotics. However, easily identifiable metabolites have been exhausted and the rediscovery of common antibiotics thwarts searches for rarer molecules. Sequencing of actinomycete genomes reveals that they contain far more biosynthetic gene clusters with the potential to encode antibiotics than whose products can be readily observed in the laboratory. The work presented in this thesis revolves around developing approaches to mine these previously inaccessible metabolites as a source of new antibiotics. First, I describe how inactivation of biosynthetic gene clusters for common antibiotics can uncover rare antibiotics otherwise masked in these strains. By applying CRISPR-Cas9 to knockout genes encoding nuisance antibiotics, I develop a simple strategy to reveal the hidden biosynthetic potential of actinomycete strains that can be used to discover rare or novel antibiotics. Second, I describe the use of the evolutionary history of biosynthetic gene clusters to prioritize divergent members of an antibiotic family, the glycopeptide antibiotics, that are likely to possess new biological activities. Using these predictions, I uncover a novel functional class of glycopeptide antibiotics that blocks the action of autolysins, essential peptidoglycan hydrolases required for remodelling the cell wall during growth. Finally, I apply target-directed genome mining, which makes use of target duplication as a predicted resistance mechanism within an antibiotic’s biosynthetic gene cluster. Using this approach, I discover the association of a family of gene clusters with the housekeeping protease ClpP and characterize the produced metabolite’s effect on ClpP function. These three research projects mine previously inaccessible chemical matter from a proven source of antibiotics, actinomycetes. The techniques and antibiotics described are required now more than ever to develop life-saving antibiotics capable of combatting multidrug-resistant pathogens.
Keywords: Antibiotics; Infectious Disease; Actinomycetes; Natural Products; Biosynthetic gene cluster; Genome mining; Autolysin; ClpP